Acute limb ischemia and aortic mural thrombosis as primary manifestations of severe acute respiratory syndrome coronavirus 2 - Szeles, Andras (J Vasc Surg Cases Innov Tech, 2021)
A variable clinical presentation is emerging as a hallmark of the novel SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2). In addition to hypoxic respiratory failure, multiorgan dysfunction, and septic shock, significant thromboembolic complications posited to result from diffuse coagulopathy have been associated with this viral infection. We report on a unique primary manifestation of SARS-CoV-2 infection presenting as acute limb ischemia and aortic mural thrombosis without clinical evidence of pulmonary disease. Despite our best attempts at limb salvage with therapeutic anticoagulation, emergent aortoiliac and distal embolectomy, the patient developed bilateral dry gangrene and ultimately required lower extremity amputations.